2011
DOI: 10.1007/s00284-011-9957-6
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Leptothrix Strain, OUMS1, from Ocherous Deposits in Groundwater

Abstract: Leptothrix species in aquatic environments produce uniquely shaped hollow microtubules composed of aquatic inorganic and bacterium-derived organic hybrids. Our group termed this biologically derived iron oxide as "biogenous iron oxide (BIOX)". The artificial synthesis of most industrial iron oxides requires massive energy and is costly while BIOX from natural environments is energy and cost effective. The BIOX microtubules could potentially be used as novel industrial functional resources for catalysts, adsorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
68
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(75 citation statements)
references
References 33 publications
4
68
1
Order By: Relevance
“…In this paper, according to the enrichment and deposition mechanism of iron and manganese [7][8][9][10][11][12], the sediment composition, the microstructure characteristics [15] and other basic research of iron bacteria, the Sphaerotilus natans which were separated from activity mud of Xiamen sewage treatment plant and the Leptothrix discophora which was purchased from ATCC, were used to deposit the iron and manganese ions respectively. The Sediments were collected and heat treated at high temperature to obtain the ferrite.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, according to the enrichment and deposition mechanism of iron and manganese [7][8][9][10][11][12], the sediment composition, the microstructure characteristics [15] and other basic research of iron bacteria, the Sphaerotilus natans which were separated from activity mud of Xiamen sewage treatment plant and the Leptothrix discophora which was purchased from ATCC, were used to deposit the iron and manganese ions respectively. The Sediments were collected and heat treated at high temperature to obtain the ferrite.…”
mentioning
confidence: 99%
“…It was shown that iron bacteria are widespread in various types of nature waters, which have the capacity of oxidizing and depositing ferrous ions and manganese ions in water efficiently. This microbe could be directly used to obtain composites with a variety of shapes such as fiber, tube and film [7][8][9][10][11][12][13][14][15][16] and has the potential to fabricate the ferrite materials. Compared to traditional chemical synthesis [5], there may be a breakthrough in the aspects of physical control, particle reunion and industrialization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When OUMS1 was cultured in silicon-glucose-peptone broth (SGP broth [13]) with a small iron plate (hereafter referred to as SGPI broth) for 3 days, a great number of the initial sheaths surrounding chained cells were seen in addition to abundant free or aggregated cells, as reported previously [6]. The adjacent, aligned cells ( Figure 2A, solid arrow) in the initial sheath comprised a faint, thin film but were not always tightly connected, and thus intercellular spaces were often observed with DIC microscopy ( Figure 2A, dotted arrow).…”
Section: Resultsmentioning
confidence: 79%
“…The genus Leptothrix, a type of Fe/Mn-oxidizing bacteria belonging to the aquatic β-proteobacteria [1][2][3], is characterized by its formation of an extracellular, tubular, Fe-or Mn-encrusted sheath, enabled by the Fe/Mn-oxidizing capacities of this genus [4][5][6]. The formation of a sheath that contains bacterial cells and extracellular metal-oxidizing activities are the two major phenotypic criteria that distinguish Leptothrix species from closely related bacteria [1,7].…”
Section: Introductionmentioning
confidence: 99%